Fenomena Beban Kerja Guru BK Non Jurusan BK dalam Mengatasi Bolos Siswa SMK Taman Siswa Binjai - Cherry Zanu Ananda; Suci Pramadani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to describe the challenges faced by non-BK Guidance and Counseling (BK) teachers in handling student absenteeism at SMK Taman Siswa Binjai. The background to this research stems from the fact that some teachers perform BK duties without formal education in Guidance and Counseling, thus experiencing various obstacles in addressing student issues, particularly truancy. This study employed a qualitative approach with a descriptive research style. The research subjects included non-BK teachers, homeroom teachers, and school officials involved in handling truancy. Data collection was conducted through observation, interviews, and documentation, while data validity was verified using triangulation of sources and methods. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results indicate that the workload of non-BK teachers at SMK Taman Siswa Binjai is high because they must fulfill dual roles as educators and implementers of BK services. Teachers not only manage teaching and learning activities and school administration but also address various student issues, including truancy. In practice, teachers face challenges in the form of a lack of counseling knowledge and skills due to a lack of formal guidance and counseling education. Steps taken to address student absenteeism include issuing warnings, recalling students, collaborating with homeroom teachers and parents, and providing ongoing guidance. Causes of student truancy include low motivation to learn, peer influence, family issues, and lack of self-discipline. Therefore, handling truant students requires collaboration between the homeroom teacher, homeroom teacher, parents, and the school to ensure effective service delivery.